2013
DOI: 10.1111/epi.12140
|View full text |Cite
|
Sign up to set email alerts
|

Seizure control and developmental trajectories after hemispherotomy for refractory epilepsy in childhood and adolescence

Abstract: SUMMARYPurpose: To evaluate the seizure control and developmental outcomes after hemispherotomy for refractory epilepsy in childhood and to identify their predictive factors. Methods: We retrospectively studied the clinical courses and outcomes of 52 children with refractory epilepsy who underwent hemispherotomy in the Epilepsy Center Freiburg between 2002 and 2011. Key Findings: Mean age at epilepsy onset was 1.8 years (range 0-8 years) and mean age at surgery was 6.7 years (range 6 months-18 years). The unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
99
3
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 28 publications
17
99
3
11
Order By: Relevance
“…The overall rate of seizure freedom was 73.4%, which is slightly higher than the rate of seizure freedom found by Holthausen et al 15 and comparable to other large, more recent series. 6,9,19,25,27,32,43 Long-term sustainability of seizure freedom is absolutely critical to justify surgery for epilepsy, which is (7) 10 (71) 2 (14) Sugimoto et al, 1999 1991-1996 Hospital for Sick Children Epilepsia (14) 33 (30) 51 (46) (continued) (27) 16 (33) 8 ( (44) 20 (21) 19 ( (42) 63 (34) 28 ( an irreversible intervention. Long-term seizure-free rates (≥ 5 years) following surgery for temporal lobe epilepsy are comparable to those reported in shorter-term studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of seizure freedom was 73.4%, which is slightly higher than the rate of seizure freedom found by Holthausen et al 15 and comparable to other large, more recent series. 6,9,19,25,27,32,43 Long-term sustainability of seizure freedom is absolutely critical to justify surgery for epilepsy, which is (7) 10 (71) 2 (14) Sugimoto et al, 1999 1991-1996 Hospital for Sick Children Epilepsia (14) 33 (30) 51 (46) (continued) (27) 16 (33) 8 ( (44) 20 (21) 19 ( (42) 63 (34) 28 ( an irreversible intervention. Long-term seizure-free rates (≥ 5 years) following surgery for temporal lobe epilepsy are comparable to those reported in shorter-term studies.…”
Section: Discussionmentioning
confidence: 99%
“…10,30,33,44 Conditions amenable to these procedures are characterized by diffuse damage to one hemisphere resulting in medically resistant epilepsy and are frequently grouped into acquired (e.g., perinatal cerebral infarction or intracranial hemorrhage, hemiconvulsion-hemiplegia-epilepsy syndrome, and other sequelae of brain trauma and infection), developmen tal (e.g., cortical dysplasia, hemimegalencephaly, and mi gration disorders), and progressive (e.g., Rasmussen's encephalitis and Sturge-Weber syndrome) etiologies. 11,27,41 The aim of this study was to systematically review the literature on hemispherectomy with emphasis on seizure outcome stratified by type of hemispherectomy and underlying etiology.…”
mentioning
confidence: 99%
“…14,19,22 Patients included in this study fulfilled the following criteria: (1) repeat resection for medically intractable epilepsy at the Epilepsy Center Freiburg, and (2) availability of comprehensive follow-up data at least 1 year after final surgery. We excluded from further analysis (1) patients with malignant brain tumors and preceding or following surgical procedures related to tumor rather than epilepsy treatment and (2) patients who underwent palliative procedures including corpus callosotomy, multiple subpial transections, or implantation of a vagal nerve stimulator.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…1 Seizure freedom following resective surgery ranges from 38% to 61% for FCD [2][3][4][5][6][7] and from 40% to 89% for glioneuronal tumors, 3,4 depending on the completeness 8 and extent of resection. 9 Thus, seizure freedom ranges from 58% to 78% in intralobar, 3,6,7 from 22% to 65% in multilobar, 3,9,10 and from 43% to 83% in hemispheric [11][12][13][14] procedures. Seizure freedom rates have been reported to be similar for infancy, childhood, and adolescence.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that shorter duration of epilepsy prior to surgery is related to a better functional outcome [6,8,9,14,17]. Hemispherotomy does not seem to worsen the gross motor impairments present before surgery [4,18,19].…”
mentioning
confidence: 99%